The viper's nest eaudiobook - Lerangis, Peter (The 39 Clues, 2017)
The most dangerous secret in Amy and Dan's past is unveiled in Book 7 of the #1 New York Times bestselling series. The hunt for 39 hidden Clues that lead to an unimaginable power have taken a heavy toll on fourteen-year-old Amy Cahill and her younger brother, Dan. They've just seen a woman die. They're wanted by the Indonesian police. They're trapped on an island with a man who knows too much about the death of their parents. And a tropical storm is rolling in. Just when they think it can't get any worse, it does. Because the Cahills have one more rattling skeleton for Amy and Dan to discover . . . the terrible truth about their family branch.